Addressing oil pollution compensation in China: an analysis of the CLC and domestic fund models - Wu, Xu; Lu, Xiaowei (Frontiers in Marine Science, 2025)
China’s current compensation mechanism for ship-source oil pollution integrates the 1992 Civil Liability Convention with a domestic compensation fund. However, it faces significant challenges in effectively addressing major oil spill incidents. The domestic fund’s collection mechanism is inflexible, and the liability cap for individual incidents is too low. Furthermore, the scope of compensation is limited, covering only emergency response expenses, cleanup costs, and direct economic losses in sectors like fishing and tourism, while neglecting long-term ecological damages. As the utilization of supertankers increases, the existing compensation system becomes inadequate to manage the risks associated with large-scale oil spills. Through a multi-dimensional analysis, this study illustrates that joining the 1992 Fund Convention would greatly enhance China’s compensation capacity. As the world’s largest oil importer, China’s anticipated annual contribution of approximately £8 million accounts for less than 0.01% of the oil industry’s profits, making it a manageable financial obligation for the industry. By adopting Canada’s dual-fund model, which unites international and domestic funds, China could create a more comprehensive compensation system that effectively addresses cross-border incidents and supports long-term ecological restoration. Acceding to the Fund Convention would provide a practical solution to marine environmental risks and reaffirm China’s strategic commitment to international responsibility, advancing the vision of a “Community of Shared Future for Mankind” in maritime governance. This transition would position China as pivotal in shaping equitable and sustainable naval policies.